2014
DOI: 10.1111/jawr.12261
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Associations of Reservoir Nutrient Characteristics and the Invasive, Harmful Alga Prymnesium parvum in West Texas

Abstract: Golden alga (Prymnesium parvum) is a harmful alga that has caused ecological and economic harm in freshwater and marine systems worldwide. In inland systems of North America, toxic blooms have nearly eliminated fish populations in some systems. Modifying nutrient profiles through alterations to land or water use may be a viable alternative for golden alga control in reservoirs. The main objective of this study was to improve our understanding of the nutrient dynamics that influence golden alga bloom formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
(78 reference statements)
0
17
0
Order By: Relevance
“…The main objective of the present study is to improve our understanding of the environmental factors associated with golden alga in reservoirs, with an overall goal of providing information useful to the development of new options for the management of golden alga in these systems. Management options discussed focus on manipulation of physicochemical characteristics of reservoirs, especially salinity‐related variables, and are distinct from options for nutrient characteristics addressed in our companion article (VanLandeghem et al ., ). To accomplish this objective, we monitored water quality and golden alga variables at a total of eight sites in the Upper Colorado River basin (UCR) in Texas from January 2010 to July 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the present study is to improve our understanding of the environmental factors associated with golden alga in reservoirs, with an overall goal of providing information useful to the development of new options for the management of golden alga in these systems. Management options discussed focus on manipulation of physicochemical characteristics of reservoirs, especially salinity‐related variables, and are distinct from options for nutrient characteristics addressed in our companion article (VanLandeghem et al ., ). To accomplish this objective, we monitored water quality and golden alga variables at a total of eight sites in the Upper Colorado River basin (UCR) in Texas from January 2010 to July 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In the field, golden alga abundance and toxicity have been shown to be correlated (Roelke et al 2012;VanLandeghem et al 2015a), but exceptions to a monotonic relationship, such as high abundance and low toxicity, have been noted in several studies (Kurten et al 2007(Kurten et al , 2010Hambright et al 2010;VanLandeghem et al 2015b). Laboratory studies have also indicated that golden alga toxicity and abundance are poorly correlated (Baker et al 2007(Baker et al , 2009Brooks et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These data were collected during standard water quality monitoring; a state‐wide golden alga survey conducted in Texas; and routine monitoring of golden alga‐impacted lakes and reservoirs. In addition, original abundance and toxicity data collected during previous projects (VanLandeghem et al 2015a,b) were included in the current analysis. In all cases, golden alga abundance was determined from hemocytometer counts following the methods of Southard (), and ichthyotoxicity was determined using a standard fathead minnow ( Pimephales promelas ) larva bioassay (Southard ).…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have documented (but not attributed) observed trends in water quality in rivers and reservoirs of Texas. These include White Rock Lake (Brandbury and VanMetre, ; Van Metre and Callender, ), Trinity River (Van Metre and Callender, ), Rio Grande (DeYoe, ; Miyazono et al ., ), Broken Bow Lake (Carroll et al ., ), Brazos River and its reservoirs (Van Landeghem et al ., ), Colorado River and its reservoirs (Van Landeghem et al ., ,b), reservoirs in the Brazos and Colorado Rivers (Patiño et al ., 2014; Dawson et al ., in review), and streams from Northeast Texas (Taylor et al ., ). The impact of hydropower on water quality has been evaluated by Ashby et al .…”
Section: Introductionmentioning
confidence: 99%